Clinical and morphological basis of two-step surgery for cataract and glaucoma - E.A. Ivachev; M.G. Fedorova (РМЖ "Клиническая офтальмология")
E.A. Ivachev1,2 M.G. Fedorova1 1Penza State University, Penza, Russian Federation 2Clinical Hospital "RZD-Meditsina" of the city of Penza, Penza, Russian Federation Aim: to provide a clinical and morphological basis for the efficacy of two-step surgery (phaco and trabeculectomy/TE) in patients with cataract and glaucoma. Patients and Methods: this study enrolled 87 patients with cataract and glaucoma. 18 patients (20.7%) were diagnosed with moderate glaucoma and 69 patients (79.3%) were diagnosed with advanced glaucoma. The intraocular pressure (IOP) was 28.4±1.4 mm Hg. Uncorrected visual acuity (UCVA) was 0.18±0.07 and best corrected visual acuity (BCVA) was 0.29±0.09. The first step was phaco with lens implantation. After 14 days, TE with scleral trephination was performed. Samples of the deep scleral flap, iris, and Tenon's capsule were collected during STE and sent for morphological examination to describe the nature of the tissue inflammatory response after cataract surgery. Results: 3 cases (3.4%) of malignant hypertension were detected after phaco. In the early postoperative period, ocular hypertension with corneal edema was diagnosed in 14 eyes (16.1%), Descemet's membrane folds in 16 eyes (18.4%), anterior chamber fibrin in 5 eyes (5.8%), and choroidal effusion in 1 eye (1.1%). After 14 days, IOP was 25.5±0.9 mm Hg, UCVA 0.5±0.06, and BCVA 0.56±0.05. After TE, hyphema and choroidal effusion were diagnosed in 29.9% (n=26) and 5.7% (n=5), respectively. One year after the two-step surgery, IOP was 18.5±1.1 mm Hg, UCVA 0.53±0.08, and BCVA 0.6±0.05. Two years after the two-step surgery, IOP was 18.8±0.7 mm Hg, UCVA 0.48±0.06, and BCVA 0.51±0.05. Morphological examination revealed signs of edema in all specimens and moderate congestion of Tenon's capsule. No cells typical of inflammation were detected. Conclusion: two-step surgery can be recommended for patients with cataract and uncontrolled glaucoma to control IOP and improve vision. Keywords: glaucoma, cataract, phacoemulsification, trabeculectomy, intraocular lens, intraocular pressure, morphological examination. For citation: Ivachev E.A., Fedorova M.G. Clinical and morphological basis of two-step surgery for cataract and glaucoma. Russian Journal of Clinical Ophthalmology. 2024;24(1):19–24 (in Russ.). DOI: 10.32364/2311-7729-2024-24-1-4.